FIFTEEN YEARS’ EXPERIENCE IN PEDIATRIC ENDOSCOPIC PROCEDURES AT THE ENDOSCOPIC SUITE OF A TERTIARY CARE HOSPITAL - ASHRAF, F; IBRAHIM, MF; QURESHI, S; GHAZANFAR, S; NIAZ, SK (Biological and Clinical Sciences Research Journal, 2023)
G.I. endoscopy is a highly efficient diagnostic and therapeutic tool now increasingly used in the pediatric population. Our country needs pediatric endoscopic data due to a lack of pediatric gastroenterologists and dedicated pediatric facilities; only a few facilities available in private setups are out of reach of the general population. Hence, this pediatric endoscopic audit was performed to analyze the indications, findings, and complications of all endoscopy procedures in a pediatric population referred to the endoscopy suite of a public sector tertiary care hospital. Data from all pediatric patients who underwent endoscopy from January 2006 to December 2020 was retrospectively reviewed for endoscopy indications, findings, and complications. Three thousand eight hundred seventy pediatric patients (age 0 -18 years) were analyzed. The mean age of the study population was 12.75 years, and the male-to-female ratio was 1.04:1. One thousand seven hundred seventy-nine patients underwent EGD, 1639 had colonoscopy, and 452 had ERCP. The most common indication for EGD was found to be epigastric pain (29.7%), the most common finding was gastritis (21.4%), and the complication rate for all upper G.I. endoscopic procedures was found to be 0.5%. The most common indication for colonoscopy was per rectal bleeding (69%), the most common finding was polyp (29.7%), and the complication rate was 0.9%. The most common indication for ERCP was found to be jaundice secondary to biliary obstruction (57.5%), the most common finding was bile duct stone (30%), and the complication rate was 5.6%. The overall incidence of adverse events was low and was found to be 0.7% in all of the 3870 procedures.